Susceptibility‐Weighted 3T MRI of the Swallow Tail Sign in Multiple Sclerosis: A Case Control Study. Issue 6 (28th August 2020) - Weber, Claudia E.; Ebert, Anne; Platten, Michael; Gass, Achim; Eisele, Philipp
ABSTRACT: BACKGROUND AND PURPOSE: The swallow tail sign describes the physiological appearance of nigrosome‐1 within the substantia nigra on high‐resolution transverse susceptibility‐weighted imaging (SWI). Previous studies demonstrated its absence in Parkinson's disease due to increasing iron content. In multiple sclerosis (MS), increased iron accumulation can be found in the brain tissue including the substantia nigra. METHODS: We investigated the swallow tail sign on high‐resolution SWI MRI in 46 MS and 23 age‐ and sex‐matched controls. RESULTS: MS patients demonstrated significantly more often an abnormal swallow tail sign (28/46; 60%) compared to controls (4/23; 17%; P = .001). In MS patients, we found no correlation between an abnormal swallow tail sign and age, disease duration or Expanded Disability Status Scale scores. CONCLUSION: The finding of an abnormal swallow tail sign in MS patients may provide an additional imaging marker even in early MS development.